Independence in the toilet activity in children and adolescents with myelomeningocele - managing clean intermittent catheterization in a hospital setting - Donlau, M.; Falkmer, Torbjorn (Wiley-Blackwell, 2009)
Aim: The aim of this study was to identify and describe gross motor, fine motor, executive andtime-processing obstacles for independence in children with myelomeningocele who are treated with Clean Intermittent Catheterization and to relate their opinions about their performance in the toilet activity, and their medical records, to the observed outcome. Methods: In a hospital setting, 22 children with myelomeningocele were observed using a structured information form while performing their toilet activity, and tested for time processing ability with the Ka-Tid instrument. Results: Only five children were independent, despite the fact that 12 of 22 children were completely satisfied with their toilet activity. Neither the degree of motor impairment, nor sex or age had any significant impact on performing the toilet activity. The ability to remain focused on the toilet activity proved to have no relation to age or learning disabilities. The medical records for the children were only able to classify approximately three quarters correctly with respect to independence. The only measurement that could suggest anything in relation to a maintained focus was time processing ability.